Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1186/s13673-017-0111-8
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative usability feature selection with ranking: a novel approach for ranking the identified usability problematic attributes for academic websites using data-mining techniques

Abstract: Objective: The aim of this study is to identify common usability problematic patterns that belong to top-50 academic websites as a whole and then ranking of these identified usability problems is also provided. Methods:In this study, a novel approach is proposed that is based upon the integration of conventional usability testing and heuristic evaluation with data-mining knowledge discovery process. An experiment is conducted to evaluate ISO 9241-151 guidelines under 16-different categories by hundred particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…Feature selection methods are used to rank features so that non-informative features can be removed to improve the classification performance [18]. Some researchers have investigated the effects of feature selection for sentiment analysis [3,[8][9][10][19][20][21][22][23][24][25]. For example, Yang and Yu [3] examine IG for feature selection and evaluate its performance using NB, SVM, and C4.5 (popular implementation for DT) classifiers.…”
Section: Related Workmentioning
confidence: 99%
“…Feature selection methods are used to rank features so that non-informative features can be removed to improve the classification performance [18]. Some researchers have investigated the effects of feature selection for sentiment analysis [3,[8][9][10][19][20][21][22][23][24][25]. For example, Yang and Yu [3] examine IG for feature selection and evaluate its performance using NB, SVM, and C4.5 (popular implementation for DT) classifiers.…”
Section: Related Workmentioning
confidence: 99%
“…12 Besides, ISO 9241-151 usability guidelines *Top Fifty Websites mentioned in National Institutional Ranking Framework are assessed under sixteen-different categories are also evaluated but by involving the end-users. 23 Association rule and decision tree techniques are administered to find functional and problematic usability features. Further, these features are prioritized by employing another ranking algorithm.…”
Section: Interaction Issuesmentioning
confidence: 99%
“…Qualitative usability assessment 8 is also done to evaluate any interactive system for a particular context of use. Further, some articles are identified that present novel study for usability assessment with data‐mining techniques like association rules and decision rules 7–9,12,23 …”
Section: Literature Reviewmentioning
confidence: 99%
“…Over the years, feature selection has been used to reduce features in diverse fields, for instance,in health care data analysis [32], flash flood hazard assessment [33], and for medical image diagnosis [34], among other applications. It has also been used in the area of software usability, for reduction of usability attributes [8,9,11], to identify problematic usability attributes [35] and to detect usability deficiencies by monitoring the amount of time taken in different tasks by users [36].…”
Section: Introductionmentioning
confidence: 99%